2014
DOI: 10.1155/2014/986230
|View full text |Cite
|
Sign up to set email alerts
|

Circumvallate Placenta: Associated Clinical Manifestations and Complications—A Retrospective Study

Abstract: Aims. To analyze the pregnancy outcomes of circumvallate placenta retrospectively and to predict circumvallate placenta during pregnancy based on its clinical features. Methods. The pregnancy outcomes of 92 women with circumvallate placenta who delivered live singletons at a tertiary care center between January 2000 and September 2012 were compared with those of 9057 controls. Results. Women with circumvallate placenta were associated with higher incidences of preterm delivery (64.1%), placental abruption (10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…When the placental ring is flat or lacks the central depression, it is called a circummarginate placenta (17). Circumvallate placenta is reported to have an increased risk of chronic placental abruption, preterm delivery, small for gestational age (SGA) status, chronic lung disease (in the child), and neonatal intensive care admissions (18).…”
Section: Circumvallate Placentamentioning
confidence: 99%
“…When the placental ring is flat or lacks the central depression, it is called a circummarginate placenta (17). Circumvallate placenta is reported to have an increased risk of chronic placental abruption, preterm delivery, small for gestational age (SGA) status, chronic lung disease (in the child), and neonatal intensive care admissions (18).…”
Section: Circumvallate Placentamentioning
confidence: 99%
“…Unlike normally developed placenta, circumvallate placenta is a type of extrachorial placenta that results from the mismatch between the basal plate and the chorionic frondosum. Consequently, the chorion inserts inward from the usual placental margin at the basal plate-frondosum junction toward the umbilical cord, resulting in a raised annular margin (1,2,(13)(14)(15)(16).This placental edge, uncovered by a villous membrane, becomes an elevated membranous fold; it appears as an ILE at the placental margin when it is discovered tangentially at US (Fig 7) (1,16).…”
Section: Circumvallate Placentamentioning
confidence: 99%
“…Partial circumvallate placenta, in which the membrane is lifted along part of the placenta, is 10-20 times more common than complete circumvallate placenta and is considered to be clinically insignificant (3). Complete circumvallate placenta, in which the membrane is lifted along the entire placental circumference, is linked to a higher incidence of fetal growth restriction, placental abruption, preterm birth, and neonatal morbidity and mortality (3,15).…”
Section: Circumvallate Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors showed that circumvallate placenta is associated with vaginal bleeding, preterm rupture of the membranes, preterm delivery, and placental abruption, the need for emergency cesarean section and also for fetal and neonatal complications such as intrauterine growth restriction, neonatal death or admission to neonatal intensive care units. [8][9][10].…”
Section: Introductionmentioning
confidence: 99%